2017
DOI: 10.1111/bph.13932
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib restores the inhibition of reverse cholesterol transport induced by inflammation: understanding the lipid paradox associated with rheumatoid arthritis

Abstract: Active inflammation could be associated with lipid accumulation within macrophages of CA rabbits. JAK inhibition induced lipid release through RCT activation, providing a plausible explanation for the effect of tofacitinib on the lipid profile of RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 68 publications
(84 reference statements)
4
32
0
Order By: Relevance
“…In agreement with this observation, in vitro experiments and in vivo animal models revealed that tofacitinib up-regulated ABCA1 expression, promoted anti-inflammatory macrophage polarization, improved EC function, and attenuated atherosclerosis (Table 1 and Fig. 3;De Vries et al, 2019;Furumoto et al, 2017;Pérez-Baos et al, 2017;Wang et al, 2017). However, recently the Oral Surveillance study revealed a statistically significant and clinically relevant increase in pulmonary embolism and an increased mortality in patients older than 50 yr with an increased CV risk when treated with a tofacitinib dose of 10 mg twice daily ( Fig.…”
Section: Anti-ifn/ifnar Signaling Therapiessupporting
confidence: 76%
“…In agreement with this observation, in vitro experiments and in vivo animal models revealed that tofacitinib up-regulated ABCA1 expression, promoted anti-inflammatory macrophage polarization, improved EC function, and attenuated atherosclerosis (Table 1 and Fig. 3;De Vries et al, 2019;Furumoto et al, 2017;Pérez-Baos et al, 2017;Wang et al, 2017). However, recently the Oral Surveillance study revealed a statistically significant and clinically relevant increase in pulmonary embolism and an increased mortality in patients older than 50 yr with an increased CV risk when treated with a tofacitinib dose of 10 mg twice daily ( Fig.…”
Section: Anti-ifn/ifnar Signaling Therapiessupporting
confidence: 76%
“…RNA was isolated according to manufacturer's protocol and cDNA was synthesized using the High-Capacity cDNA Reverse Transcription Kit (Applied Biosystems, USA). TaqMan Gene expression assays were used to quantify mRNA expression in StepOnePlus™ detection system using StepOne™ software v2.2 (Applied Biosystems) ( 19 , 34 ). HPRT was used as endogenous control and data was presented as relative expression to IL-1β and TNFα-stimulated chondrocytes or to healthy rabbits.…”
Section: Methodsmentioning
confidence: 99%
“…Human LDL were isolated from fresh plasma by sequential ultracentrifugation (34). After removing VLDL and IDL at 1.019 g/ml, LDL fraction between 1.019 and 1.063 g/ml was collected.…”
Section: Ldl Isolation and Cell Treatmentmentioning
confidence: 99%
“…The study also confirmed the role IFN-γ in formation of foam cells, representing the key element for development of atherosclerosis. Inhibition of JAK/STAT pathway by tofacitinib contributed to lipid release via enhanced expression of cellular liver X receptor α and ATP-binding cassette transporter (ABCA1) synthesis [ 83 ]. Similarities in mechanisms of action in those two studies may suggest the role of IL-6 as a mediator of changes in lipid metabolism.…”
Section: Safety Issues Of Jak Inhibitorsmentioning
confidence: 99%